Theory of sample surveys - Thompson, M. E. (Mary Elinore) (Monographs on statistics and applied probability (Series), 1997)
Discusses the theory of sample surveys for descriptive aims. After narrowing the focus to the study of sampling error, the book concentrates on the mechanics of design-based estimation. It then covers inference itself, and moves on to an examination of analytical purposes in surveys.